Exploration Of The Potential Of Pharmaceutical Services Online Apotek X Jatiwaringin Bekasi Based Blue Ocean Strategy (Bos) - Atika Bendra; Sahat Saragi; Lies Putriana (SEAN Institute, 2023)
One of the impacts of the development of information technology and the emergence of the Covid-19 pandemic is the emergence of various digital platforms in health services, including pharmaceutical services. The business model has completely changed and has an impact on the importance of adjusting relevant business strategies. Pharmacy X is one of the business units that is experiencing the dynamics of the impact of technology and the COVID-19 pandemic on its business performance. This study aims to formulate an appropriate business strategy for optimizing performance development through the X Jatiwaringin Bekasi Pharmacy service using the Blue Ocean Strategy approach. The research method used was qualitative, with a total of 7 informants (5 pharmacy managers and 2 customers). Data collection was carried out through in-depth interviews and supplemented by field observation data and pharmacy performance reports. Data were analyzed using SWOT analysis with a blue ocean strategy approach. The SWOT analysis and the four-step framework using the blue ocean strategy approach conclude that there are no factors that need to be eliminated, because all the factors that exist in Pharmacy X are currently needed. Factors that must be improved include service quality, product completeness and availability, as well as consulting services that have been implemented. Product prices are a factor that needs to be lowered, especially for fast moving drugs because there are quite a lot of consumers and they are one of the mainstay products of the Pharmacy. Meanwhile, the factors that must be created are information systems, collaboration or joining digital platforms, online payment methods, inventory systems, and promotional programs that are more diverse and digital-based promotions.